1994
DOI: 10.1002/cyto.990150310
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human papillomavirus type 16/18 DNA in cervicovaginal cells by fluorescence based in situ hybridization and automated image cytometry

Abstract: Automatic fluorescence image cytometry (AFIC) is a fast, sensitive, and reliable approach for screening slide-based clinical specimens. In this study, we applied AFIC to identify cancer-associated human papillomavirus (HPV) genotypes 16 and 18 in individual cells of cervical smears using a sensitive fluorescence based in situ hybridization (FISH) assay. HPV sequences were labeled by FISH and the cells imaged using an epi-fluorescence microscope coupled to a low-light color CCD camera. Before application to cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Labeling of the full-length DNA insert with digoxigenin using nick-translation (Boehringer Mannheim) resulted in a lower signal in CaSki cells compared with the D-DNA probe (data not shown). Method 1 enabled us to detect as few as one to five copies of HPV-16 in 100% of SiHa cells ( Figure 2C) compared with 60% for Method 2 (data not shown) (22). Lack of signal in C33-A and HT-3 cells (data not shown) with the D-oligo ( Figure 2D) and the D-DNA probes (data not shown) demonstrates the specificity of the probe labeling.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Labeling of the full-length DNA insert with digoxigenin using nick-translation (Boehringer Mannheim) resulted in a lower signal in CaSki cells compared with the D-DNA probe (data not shown). Method 1 enabled us to detect as few as one to five copies of HPV-16 in 100% of SiHa cells ( Figure 2C) compared with 60% for Method 2 (data not shown) (22). Lack of signal in C33-A and HT-3 cells (data not shown) with the D-oligo ( Figure 2D) and the D-DNA probes (data not shown) demonstrates the specificity of the probe labeling.…”
Section: Resultsmentioning
confidence: 90%
“…This assessment demonstrated that our AFIC had a linear response, was quantitatively accurate, and had the sensitivity to detect one to five HPV genomes per nucleus (22). Because of the linearity of AFIC, we were able to collect images with different integration times, normalize the data, and subsequently compare them (Table 2).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The images are stored digitally in computer memory from where they are accessible for analysis by software algorithms. IC is now a primary technique for understanding normal and pathological cellular mechanisms, because it is possible to quantitatively and nondestructively measure wide ranges of biochemical, morphological, densitometric, and contextual parameters on the individual cells and nuclei in the specimens (2,10,21,23,24,25,29,38,40).The convenient measurement of many individual nuclei requires image analysis algorithms that automatically locate every nucleus. This i s usually accomplished by staining the nuclei in such a way that their corresponding image intensities are significantly different from the background intensities.…”
mentioning
confidence: 99%
“…The images are stored digitally in computer memory from where they are accessible for analysis by software algorithms. IC is now a primary technique for understanding normal and pathological cellular mechanisms, because it is possible to quantitatively and nondestructively measure wide ranges of biochemical, morphological, densitometric, and contextual parameters on the individual cells and nuclei in the specimens (2,10,21,23,24,25,29,38,40).…”
mentioning
confidence: 99%